FORMS OF JUSTICE AND CRIMINAL LEGAL PROTECTION FOR CHILDREN THROUGH DIVERSION IN THE FUTURE - Darwanto; Sudarsono; Abdul Madjid; Bambang Sugiri (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Children are a gift from God Almighty, potentially as the next generation to continue the ideals of the struggle of the Indonesian nation, so that they have the right to survive, grow and develop. For this reason, children are considered to need to be given physical and spiritual protection, because every child who is in conflict with the law is always sentenced to imprisonment, even though imprisonment has not gained the trust of the community, thus causing problems. The background underlying this writing is the application of diversion in resolving cases involving children as perpetrators of criminal acts who are sentenced to more than 7 years. Concretely, the problem raised in this writing is how the form of child justice protection through diversion and how the legal regulations on diversion in Indonesia are just. This writing uses a normative research method with a statute approach. Through analysis with this method, it can be seen that the provisions of diversion which are legally regulated in the Republic of Indonesia Law Number 11 of 2012 concerning the Juvenile Justice System have been able to be carried out starting from the investigation stage and the results of the diversion agreement are issued in the form of a Court Decision, and there is an expansion of several articles in the Republic of Indonesia Law Number 11 of 2012 concerning the Juvenile Justice System which is further regulated in the Regulation of the Supreme Court of the Republic of Indonesia Number 4 of 2014 concerning Guidelines for the Implementation of Diversion in the Juvenile Criminal Justice System. However, in the continuation regulated by Perma Number 4 of 2004, it does not explicitly regulate the maximum criminal limit for juvenile criminals set above 7 (seven) years